Tan Sri Professor Dr. Muhammad Abdul Rauf: on good character - Hassan @ Mohamed, Nor Jana (OFIIR-CENTRIS, 2024)
Tan Sri Professor Dr. Muhammad Abdul Rauf served as the IIUM’s first Rector from 1983 to 1988. He was an epitome of the IIUM, a towering yet humble scholarly figure of the budding garden that was soon to bloom into a “Garden of Knowledge and Virtue”. A global academic and humanitarian, he strove to be the best that he could ever be and contributed as much as he ever could for humanity, bridging between the East and the West – in Malaysia, the Arab world, in the Western lands and in Africa – wherever he was, with mercy (Raḥmah).Muhammad Abdul Rauf, like the IIUM, the first international Islamic university of the contemporary world for which he served and represented as her first Rector, was truly beyond global. Comparable to the numerous devout Muslim scholars and intellectuals of earlier eras carrying the message of Raḥmatan li’l-‘Ālamῑn (Mercy to all the Worlds) of the blessed Prophet Muhammad (ṣ‘aw), Muhammad Abdul Rauf was indeed universal (al-‘ālamῑn). He passed away on December 11th, 2004, at the age of 87.